2016
DOI: 10.2337/db15-1563
|View full text |Cite
|
Sign up to set email alerts
|

Hsp20-Mediated Activation of Exosome Biogenesis in Cardiomyocytes Improves Cardiac Function and Angiogenesis in Diabetic Mice

Abstract: Decreased heat shock protein (Hsp) expression in type 1 and type 2 diabetes has been implicated as a primary factor contributing to diabetes-induced organ damage. We recently showed that diabetic cardiomyocytes could release detrimental exosomes, which contain lower levels of Hsp20 than normal ones. To investigate whether such detrimental exosomes could be modified in cardiomyocytes by raising Hsp20 levels to become protective, we used a transgenic (TG) mouse model with cardiac-specific overexpression of Hsp20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
180
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(188 citation statements)
references
References 33 publications
7
180
1
Order By: Relevance
“…These results suggest a role for Hsp20 in inhibiting Ucp-1-dependent thermogenesis in adipocytes. However, it has been reported that Hsp20 can be found in exosomes released into the circulation, raising the possibility of cross-talk between organs (Wang et al, 2016). To investigate whether Hsp20 regulates the thermogenic program in a cell-autonomous manner, we isolated stromal vascular cells (SVCs) from iWAT of WT and KO mice.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest a role for Hsp20 in inhibiting Ucp-1-dependent thermogenesis in adipocytes. However, it has been reported that Hsp20 can be found in exosomes released into the circulation, raising the possibility of cross-talk between organs (Wang et al, 2016). To investigate whether Hsp20 regulates the thermogenic program in a cell-autonomous manner, we isolated stromal vascular cells (SVCs) from iWAT of WT and KO mice.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with mimics of these miRNAs decreased expression of matrix metalloprotease 9 (MMP-9), a protein linked to adverse cardiac remodeling in response to stress [53]. Exosomes released during diabetic cardiomyopathy carry miR-320, which downregulates expression of HSP20 [54]. Decreasing levels of heat shock proteins is thought to be a major cause of cellular dysfunction.…”
Section: Cardiac Exosomesmentioning
confidence: 99%
“…Using a streptozotocin (STZ) diabetes induced mouse model, it was found that overexpression of HSP20 significantly reduced cardiac dysfunction and triggered greater exosome production; these exosomes carried higher levels of HSP20, survivin, and p-Akt [54]. In vitro treatment of cardiac myocytes and endothelial cells with these exosomes reduced oxidative stress; in vivo treatment decreased adverse cardiac remodeling in the STZ mouse model [54]. Pressure overload in mice led to the release of exosomes containing angiotensin II type I receptor (AT1R).…”
Section: Cardiac Exosomesmentioning
confidence: 99%
“…As effect of PKA inhibition and PKD1-HSPB6 complex disruption on HSPB6 phosphorylation was indicated additive, the hypothesis is that the functional roles of HSPB6 associated with its phosphor-Ser16 status result from two opposing kinase activation within 'sub-pools' of HSPB6. The balance between PKA and PKD1 activation is thus likely to cue the consequence of a hypertrophic response Cardiac-specific overexpression of HSPB6 also remarkably attenuated diabetes-induced cardiac dysfunction and adverse remodeling [80]. Interestingly, elevation of HSPB6 levels not only increased secretion of protective exosomes but also reprogrammed detrimental exosomes generated in cardiomyocytes [80].…”
Section: Anti-hypertrophic Actionmentioning
confidence: 99%
“…The balance between PKA and PKD1 activation is thus likely to cue the consequence of a hypertrophic response Cardiac-specific overexpression of HSPB6 also remarkably attenuated diabetes-induced cardiac dysfunction and adverse remodeling [80]. Interestingly, elevation of HSPB6 levels not only increased secretion of protective exosomes but also reprogrammed detrimental exosomes generated in cardiomyocytes [80]. As exosome has been well studied as a critical tool for cell-to-cell communication [81], the HSP-mediated intrinsic protective message could be spread out via exosomes to whole tissue/organ, even whole body.…”
Section: Anti-hypertrophic Actionmentioning
confidence: 99%